Sao Tome and Principe : Country Gender Assessment - World Bank (Washington, DC, 2013)
The purpose of the Sao Tome and Principe Country Gender Assessment is to create an analytical tool to analyze the main gender issues; develop a body of proposals and recommendations covering a range of interventions specifically addressing gender issues and, to establish dialogue and coordination between representatives of the public sector and civil society, with a view to developing a National Gender Strategy and Action Plan. The preparation of the Country Gender Assessment (CGA) included two stages. The first comprised a review of all available documentation and data related to gender issues. The second consisted of consultations with government, non-governmental organization s (NGOs), members of civil society, and donors. These consultations led to a two-day workshop with participation by representatives of various Ministries, as well as other government agencies, district councils, civil society members and NGOs. The purpose of the workshop was to obtain input from the participants in the form of a body of proposals for plans and initiatives covering areas considered of high priority, with a view to enhancing the effectiveness of development programs and projects. The CGA is by its nature an ongoing activity rather than a defined product.